Smart Supramolecular Nanosystems for Bioimaging and Drug Delivery. Issue 1 (5th December 2014) - Yang, Peipei; Wang, Lei; Wang, Hao
Abstract The application of smart supramolecular nanosystems in biomedicine increases rapidly and offers promising prospects for disease diagnostics and therapeutics. Supramolecular nanosystems such as liposomes, micelles, organic nanoaggregates and metallic nanostructures etc. have been widely explored as diagnostic/therapeutic tools. Here, we review the recent advances in supramolecular nanosystems with different built‐in reporters, e.g., fluorescent, magnetic and photoacoustic signals for bioimaging. In addition, the substantial progress of supramolecular nanosystems as drug delivery carriers for cancer therapy, including chemotherapy, photothermal and photodynamic therapies is also summarized.